SAT0066 The long noncoding rna (LNCRNA) hottip is a master regulator of cell cycle in hand synovial fibroblasts in arthritis - Frank Bertoncelj, M.; Masterson, T.; Karouzakis, E.; Kolling, C.; Filer, A.; Buckley, C.D.; Gay, S.; Distler, O.; Ospelt, C. (Annals of the rheumatic diseases, 2018)
BackgroundRheumatoid arthritis (RA) and other types of inflammatory arthritis follow a characteristic anatomical pattern of joint involvement. We have recently shown that local synovial stromal cells, specifically synovial fibroblasts, exhibit joint-specific transcriptomes and functions. In particular, hand SF exhibited prominent proliferative and chemotactic activities. Density of stroma and leukocyte infiltration were increased in hand synovium.ObjectivesTo explore the role of hand/feet-specific lncRNA HOTTIP in shaping the function of hand synovial fibroblasts in arthritis.MethodsWe studied transcriptomes and epigenomes of hand, shoulder and knee SF from patients with RA or osteoarthritis and from knees of non-arthritic subjects using RNA-sequencing, Illumina HiSeq 2000 n=21), histone ChIP-sequencing (Illumina HiSeq 2500, n=7) and Infinium HumanMethylation450 BeadChip (n=12). qPCR was used to confirm RNA-sequencing data in a larger cohort of SF from different joints. We silenced the lncRNA HOTTIP in hand SF using LNA GapmeRs, followed by RNA-sequencing, qPCR, protein-protein interaction analysis of RNA-sequencing data (STRING), and in vitro assays for proliferation (BrdU assay) and apoptosis (Annexin V/PI staining).ResultsGenome-wide DNA methylation patterns and histone marks at actively transcribed DNA regions (H3K27ac) and enhancers (H3K4me1) defined joint-specific origin of SF. SF from hands and feet specifically expressed the lncRNA HOTTIP. This distal-specific HOTTIP expression coincided with the enrichment of H3K4me3 and H3K27ac and a decrease in repressive marks (H3K27me3, DNA methylation) at the HOTTIP promoter in hand SF. In contrast, the HOTTIP promoter displayed scarce activating, but abundant repressive epigenetic marks in shoulder and knee SF. Silencing of HOTTIP in hand SF altered the expression of 447 protein-coding genes (log ratio >|2|, FDR<0.05). These genes were strongly enriched in the mitotic cell cycle protein interaction network (n=48 genes, p=3.3x10–7). Several of the enriched mitotic cell cycle genes, including NCAPG, CENPO, ZWILCH and BUB1 were confirmed as downregulated by HOTTIP silencing in a larger cohort of hand SF (n=6). The basal expression of 36 out of the 48 enriched cell cycle genes correlated with the basal HOTTIP expression in hand SF (n=6, RNA-sequencing, R>|0.06|). We further measured these correlations in a larger cohort of hand SF (n=21) for a subset of the 36 genes using qPCR. Among the measured genes, TADA 3 and CDC27 were confirmed to correlate with HOTTIP expression in hand SF (R=0.5, p<0.05). Silencing of HOTTIP for 24 hour, 48 hour and 72 hour decreased the incorporation of BrdU into DNA of hand SF as measured by BrdU proliferation assay (p<0.05, n=3). Apoptosis of hand SF increased at 48 hour of HOTTIP silencing (p<0.05, n=3).ConclusionsThe lncRNA HOTTIP, which is specifically expressed in hand joints via epigenetic mechanisms, is a master regulator of mitotic cell cycle genes and proliferation in hand SF. Distal-specific expression of HOTTIP might imprint hand SF with enhanced proliferative potential, thereby shaping the location-specific joint pathology, e.g. prominent synovial hyperplasia and increased severity of hand arthritis in RA.Disclosure of InterestM. Frank Bertoncelj Grant/research support from: euroTEAM, BTCure, IRR, Promedica, Georg und Berta Schwyzer Winiker Grant, T. Masterson: None declared, E. Karouzakis Grant/research support from: BTCure, GSK, C. Kolling: None declared, A. Filer: None declared, C. Buckley: None declared, S. Gay Grant/research support from: euroTEAM, BTCure, GSK, IRR, O. Distler Grant/research support from: Abbvie, Actelion, Bayer, BiogenIdec, Boehringer Ingelheim, ChemomAb, espeRare foundation, Genentech/Roche, GSK, Inventiva, iQone, Lilly, medac, MedImmune, Mepha, MSD, Mitsubishi Tanabe Pharma, Novartis, Pfizer, Pharmacyclics, Sanofi, Sinoxa and UCB, Consultant for: Abbvie, Actelion, Bayer, BiogenIdec, Boehringer Ingelheim, ChemomAb, espeRare foundation, Genentech/Roche, GSK, Inventiva, iQone, Lilly, medac, MedImmune, Mepha, MSD, Mitsubishi Tanabe Pharma, Novartis, Pfizer, Pharmacyclics, Sanofi, Sinoxa and UCB, C. Ospelt Grant/research support from: euroTEAM, BTCure, CABMM, IRR, Promedica